Using the Expected Monetary Value (EMV) Method to Minimize Risk in Project Decision Making - Harahap, Lokot Muda; Sinaga, Christin Lestari; Lubis, Devi Aprilia; Sampurno, Muhammad Akbar; Nelfita, Natasyah (Economic: Journal Economic and Business, 2023)
Effective decision making is key to achieving project success. Risk is always present in managing projects and can significantly impact the final outcome. The Expected Monetary Value (EMV) method is an important tool in managing project risk. EMV is used to calculate the monetary value of the various possible outcomes of a decision or series of decisions. In the context of project decision making, EMV helps project managers to estimate the monetary value of the risks associated with various decisions to be taken during the project cycle. This research uses a literature review type of study and the review model chosen is a narrative review. This research was conducted using a narrative review model. The research method used is secondary data collected from various international journals, papers, and previous research papers used as data sources and analyzed by the author taking into account the problems considered in this research.